Pengaruh Program Membaca Kelas terhadap Kemampuan Menulis Naratif Siswa Sekolah Dasar - Yaningsih, Yunita Fitri; Cahyaningtyas, Andarini Permata (Jurnal Gentala Pendidikan Dasar, 2025)
The key to students' early literacy success lies in effective learning strategies. Improving narrative writing skills in elementary school students is a crucial benchmark in developing their thinking and expressive abilities. Therefore, this article aims to examine the impact of the Classroom Reading Program (CRP) on the narrative writing skills of elementary school students. The research method uses a descriptive qualitative literature review. Data was obtained through the compilation and content analysis of various relevant literature. To ensure the accuracy of the study and prevent misinformation in data analysis, triangulation was performed among literary sources. This research found that the consistent use of CRP has a proven positive and significant influence on enhancing the narrative writing skills of elementary school students. This improvement is evident in students' ability to construct coherent story plots, use varied sentence structures, and select appropriate diction. In other words, CRP offers a conception of an effective integrated learning model as an effort to optimize the provision of early writing literacy in Indonesia.